Agile Dynamics at Scale. Issue 2 (5th July 2018) - Markina‐Khusid, Aleksandra; Moulton, Allen; Howard, Greg; James, John H.; Mahoney, Paula J.; Ricks, Sean
ABSTRACT: Wider adoption of Lean‐Agile software development methods has prompted interest in tailoring these small team methods to meet the needs of larger organizations. The Scaled Agile Framework (SAFe) for Lean Software Development incorporates many Lean‐Agile best practices and has become a leading proposition for applying agile methods at scale (Leffingwell 2016). To help managers visualize how SAFe might work for their organization, we have created a management flight simulator based on a system dynamics model of SAFe. Using these tools, decision makers who consider transitioning their organizations to SAFe can perform virtual experiments by changing parameters such as team size, developer experience level, sprint length, and whether developers perform continuous integration to explore how these programmatic decisions affect the rate at which work is completed. Such process prototyping can provide a justification for adopting SAFe, which often includes costly training and organizational restructuring, by forming a basis for quantifying return on investment. We applied our system dynamics model to a real program and showed that instituting continuous integration can improve throughput by 54% while decreasing defects by 88%.